Motivated, Fit, and Strong—Using Counter‐Stereotypical Images to Reduce Weight Stigma Internalisation in Women with Obesity. Issue 2 (12th November 2019) - Myre, Maxine; Berry, Tanya R.; Ball, Geoff D.C.; Hussey, Brad
Abstract : Background: This study aimed to use implicit retraining to change automatic associations between body size and physical activity (PA) in women with obesity to reduce weight bias internalisation (WBI). Methods: A Solomon‐square experimental design was used to determine the effect of a four‐week online implicit retraining intervention on WBI (primary measure) and PA attitudes, self‐efficacy, and self‐reported behaviour (secondary measures). The intervention was a visual probe task pairing counter‐stereotypical images of active individuals with obesity with positive PA‐related words. In qualitative telephone interviews, a sub‐sample of participants provided feedback and recommendations for using counter‐stereotypical images in PA promotion. Results: Women completed the intervention ( n  = 48) or a control task ( n  = 55). Results of a RM‐ANOVA showed no interaction or main effect of group on WBI. A main effect of time demonstrated that both groups had reduced WBI between pre‐test and post‐test, through to one‐week follow‐up. There were no differences between groups or over time for PA attitudes, self‐efficacy, or behaviour. Women who completed interviews ( n  = 16) discussed several benefits and drawbacks of using counter‐stereotypical images. Conclusion: Implicit retraining did not reduce WBI but qualitative findings support the use of counter‐stereotypical PA images.